PARTISIPASI PEREMPUAN DALAM PENGELOLAAN BUMG DI GAMPONG BLANG KRUENG KECAMATAN BAITUSSALAM KABUPATEN ACEH BESAR - Zalikha, Siti Nur; Mahmuddin; Fatmawati (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
The village is the foremost and closest government agent and is able to directly touch the interests of the community. One of its efforts is through the establishment of Village-Owned Enterprises (BUMDes), which in Aceh are called the Village-Owned Enterprises (BUMG). In its management, BUMG has several management principles, one of which is participation. Therefore, women also have the right to participate in the management of BUMG. Blang Krueng Village is one of the villages that has the best BUMG in Aceh and the 2016 National level of participation category. This study aims to look at the participation of women in the management of BUMG in Blang Krueng Village and the factors that influence women's participation in the management of BUMG in Blang Krueng Village. In this study, researchers used descriptive qualitative research. Based on the results of the study, it was found that the management of BUMG Blang Krueng Village has involved women in the planning process, delivery of aspirations, implementation and evaluation. In organizing, women are also involved as managers. It can be seen from 11 (eleven) business units that have been established, there are 5 (five) Blang Krueng BUMG business units which are chaired by women